Development and pilot testing of a psychosocial intervention program for young breast cancer survivors. Issue 3 (March 2016) - Ahmed, Kauser; Marchand, Erica; Williams, Victoria; Coscarelli, Anne; Ganz, Patricia A.
Highlights: CDC funding led to creation of psychosocial intervention for YBCS. Community needs assessment revealed gaps in services and needs of young survivors. Psychosocial intervention developed and pilot tested. 5 workshops delivered—results showing gain in confidence, ability, and knowledge. LABC is unique, connecting young survivors and teaching skills for survivorship. Abstract: Objective: To describe the development, pilot testing, and dissemination of a psychosocial intervention addressing concerns of young breast cancer survivors (YBCS). Methods: Intervention development included needs assessment with community organizations and interviews with YBCS. Based on evidence-based models of treatment, the intervention included tools for managing anxiety, fear of recurrence, tools for decision-making, and coping with sexuality/relationship issues. After pilot testing in a university setting, the program was disseminated to two community clinical settings. Results: The program has two distinct modules (anxiety management and relationships/sexuality) that were delivered in two sessions; however, due to attrition, an all day workshop evolved. An author constructed questionnaire was used for pre- and post-intervention evaluation. Post-treatment scores showed an average increase of 2.7 points on a 10 point scale for the first module, and a 2.3 point increase for the second module. Qualitative feedback surveys were also collected. The two community sites demonstrated similar gains among their participants. Conclusions: The intervention satisfies an unmet need for YBCS and is a possible model of integrating psychosocial intervention with oncology care. Practice implications: This program developed standardized materials which can be disseminated to other organizations and potentially online for implementation within community settings.